An updated meta-analysis of MitraClip versus surgery for mitral regurgitation - Oh, Nicholas A.; Kampaktsis, Polydoros N.; Gallo, Michele; Guariento, Alvise; Weixler, Viktoria; Staffa, Steven J.; Avgerinos, Dimitrios V.; Colli, Andrea; Doulamis, Ilias P. (Annals of Cardiothoracic Surgery, 2020)
Background: Although studies demonstrate its feasibility, there is ongoing debate on the short and long-term outcomes of MitraClip versus surgical repair or mitral valve replacement (MVR). The objective of this meta-analysis is to compare the safety, morbidity, mortality and long-term function following MitraClip compared to MVR. Methods: Articles were searched in Pubmed and Cochrane databases for studies comparing outcomes of MitraClip and surgery on December 1, 2019. Eligible prospective, retrospective, randomized and non-randomized studies were reviewed. Results: A total of nine studies (n=1,873, MitraClip =533, MVR =644) were eligible for review. At baseline, MitraClip patients had more comorbidities than MVR patients, including myocardial infarction (P